« Le loup-garou des légendes est aujourd’hui dépassé ». L’écho chanté d’un tueur de bergers (1895-1898) - Marc Renneville (Criminocorpus)
The criminal ballad differs from the news item ballad only in its subject matter, but what about the ballad dealing with a particularly atrocious crime? Isn't the strong collective emotion a challenge for the ballad? Can horror be sung? This article proposes an answer based on the corpus of ballads dealing with the Vacher affair. An analysis of the texts shows that the ballad does not need to adapt its composition to the treatment of criminal horror. This ability to recount the unspeakable contributes to its continued strong presence at the end of the 19th century, when the printed newspaper was tending to achieve maximum circulation in France.